Urgency of Guarantee in Cancellation of Payment of Goods Price in Sale and Purchase Agreement through Marketplace - Zainuri Zainuri; Evi Dwi Hastri (Civiliza Publishing, 2026)
This study analyzes the legal vacuum in the legal arrangement of sale and purchase agreements on the existence of guarantees. Meanwhile, in the era of digital transformation, it is increasingly complex. In transacting, the development has used non-conventional methods such as buying and selling online through a marketplace with a Cash On Delivery (COD) system. This phenomenon requires the law to be more adaptive in responding. So the purpose of this study is to analyze and examine in depth the urgency of a guarantee in the legal relationship of the sale and purchase agreement on the cancellation of the payment of the price of goods made online through the marketplace. The type of research used is normative juridical. The results of the study show that legal reconstruction is needed to meet the urgency of guarantees. This can be expressed in giving rise to the legal concept of guarantee in the legal relationship of the sale and purchase agreement because there is a loss experienced by the seller for default committed by the buyer by deliberately not paying and canceling the price of the goods that have been agreed. Prof. Satjipto Rahardjo's progressive legal theory is considered very relevant in supporting this concept outside the concept of the use of collateral which is still limited to credit agreements or debts and receivables. Given the complexity of onrechtmatige daad in online buying and selling agreements, it is quite common.